Finite Deformation of Nonlinearly Elastic Ring - Wegner, T.; Magnucki, K.; Wasilewicz, P. (Engineering Transactions, 1987)
The object of this paper is the analysis of compression of a ring made of incompressive material having nonlinear properties, described by the Mooney's equation. The case of compressing a ring without sliding between two plane rigid plates was discussed. The resolution of the problem for finite deformations using the hypothesis of plane sections was obtained by way of numerical minimizing the strain energy of a discrete model of a ring.